2008
DOI: 10.1038/jcbfm.2008.111
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Wnt Antagonist, Dickkopf-1, Contributes to the Development of Neuronal Death in Models of Brain Focal Ischemia

Abstract: Inhibition of the canonical Wnt pathway has been implicated in the pathophysiology of neuronal death. Here, we report that the secreted Wnt antagonist, Dickkopf-1 (Dkk-1) is rapidly induced in neurons after induction of focal brain ischemia. In rats undergoing transient focal ischemia in response to brain infusion of endothelin-1, Dkk-1 was induced in neurons of the ischemic core and the penumbra region. Induction of Dkk-1 was associated with a reduced expression of b-catenin (a downstream signaling molecule o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 67 publications
4
89
1
Order By: Relevance
“…Chronic stress or increased corticosteroids are known to induce DKK-1 expression and neuronal damage in the hippocampus (81), which is required for ischemic neuronal death (82). DKK-1 also mediates glucocorticoid-induced changes in human neuronal progenitor cell growth and differentiation (83), adding support to the finding that DEX stimulates DKK-1 gene expression in TG.…”
Section: Discussionsupporting
confidence: 60%
“…Chronic stress or increased corticosteroids are known to induce DKK-1 expression and neuronal damage in the hippocampus (81), which is required for ischemic neuronal death (82). DKK-1 also mediates glucocorticoid-induced changes in human neuronal progenitor cell growth and differentiation (83), adding support to the finding that DEX stimulates DKK-1 gene expression in TG.…”
Section: Discussionsupporting
confidence: 60%
“…In our system, Dkk1 reversibly affects the number of synapses without affecting programmed cell death. Interestingly, previous studies have indicated that increased Dkk1 levels contribute to cell death in cerebral ischemia (Cappuccio et al, 2005;Mastroiacovo et al, 2009), epilepsy (Busceti et al, 2007) and neurodegenerative diseases (Scali et al, 2006;Rosi et al, 2010). This apparent discrepancy could be explained by the low level and short-term treatment with Dkk1 used in our system.…”
Section: Discussioncontrasting
confidence: 41%
“…The drug PHCCC (10 mg/kg) was administered subcutaneously 20 minutes after Et-1 infusion, and ischemic damage was assessed 3 days later (Moyanova et al, 2007;Mastroiacovo et al, 2009). The drug reduced the infarct volume by 35% to 40% as compared with control animals; this reduction was prominent in subcortical regions ( Figures 3A and 3B).…”
Section: Pharmacological Activation Of Metabotropic Glutamate-4 Recepmentioning
confidence: 97%